Evaluation of Posterior Superior Alveolar Canal on Cone Beam Computed Tomography Images - Vasegh, Zahra; Valizadeh, Solmaz; Safi, Yaser; Ghazizadeh Ahsaie, Mitra; Mohammadi, Yasaman (Journal of Dental School, 2020)
Objectives The posterior superior alveolar artery (PSAA) is one of the branches of the maxillary artery that is located on the lateral wall of the maxillary sinus. The aim of the present study was to evaluate the detectability, position, and diameter of the posterior superior alveolar (PSA) canal and its relationship with the alveolar ridge using cone-beam computed tomography (CBCT). Methods A total of 257 CBCT images were evaluated. The PSA canal location was categorized into three forms of intra-osseous, below the membrane, and on the outer cortex of the lateral sinus wall. The distance between the lower border of the artery and the alveolar crest, the distance between the artery and the medial wall of the sinus, and the diameter of the artery were all measured. The prevalence of sinusitis and mucous retention cyst was also determined. The Chi-square test and independent t-test were used for statistical analysis. Results The most common type of PSA canal was intra-osseous, followed by beneath the mucosal membrane and on the outer cortex of the lateral sinus wall. The lowest distance between the PSA canal and medial sinus wall and ridge crest, and canal diameter were higher in males (P<0.05). In addition, sinus pathologies were significantly more common in males than females (P<0.05). Conclusion The most common type of PSA canal was intra-osseous, and the distances between the lower border of the canal and the alveolar crest and ridge height decreased with aging; thus, it should be considered during implant surgery.